2013
DOI: 10.1118/1.4823795
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a measurement‐based source model for kilovoltage cone‐beam CT Monte Carlo dosimetry simulations

Abstract: Purpose: The purpose of this study is to adapt an equivalent source model originally developed for conventional CT Monte Carlo dose quantification to the radiation oncology context and validate its application for evaluating concomitant dose incurred by a kilovoltage (kV) cone-beam CT (CBCT) system integrated into a linear accelerator. Methods: In order to properly characterize beams from the integrated kV CBCT system, the authors have adapted a previously developed equivalent source model consisting of an equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…These discrepancies may be caused by some specific settings in Spektr and SpekCalc related to the manufacturers’ specifications of x-ray tubes, which are not available to us. McMillan et al have also reported that their measurement-derived spectra for cone-beam CT were more than 10% harder than the spectra extracted with Spektr (McMillan et al , 2013). …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These discrepancies may be caused by some specific settings in Spektr and SpekCalc related to the manufacturers’ specifications of x-ray tubes, which are not available to us. McMillan et al have also reported that their measurement-derived spectra for cone-beam CT were more than 10% harder than the spectra extracted with Spektr (McMillan et al , 2013). …”
Section: Resultsmentioning
confidence: 92%
“…Source modeling has been widely used in modern radiation therapy treatment planning dose calculation in patient anatomy for MV treatment systems such as linear accelerators (Chetty et al , 2000; Deng et al , 2000), Tomotherapy (Yuan et al , 2015) and CyberKnife (Deng et al , 2003; Deng et al , 2004), as well as kV imaging system such as kVCBCT (Spezi et al , 2011; McMillan et al , 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The approach of using a combination of two beam quality indicators has been validated by other groups who have used it successfully to characterize the spectrum of an x‐ray beam for Monte Carlo dose computations using HVL 1 and kVp in one instance and HVL 1 and HVL 2 in another …”
Section: Methodsmentioning
confidence: 99%
“…The method to measure the bowtie filter geometry is similar to that proposed by McMillan et al [41]. 2) where µ is the energy dependent attenuation coefficient, µ en is the energy absorption coefficient, and d air is the air thickness in the dosimeter.…”
Section: Appendix a Characterization Of Bowtie Filtersmentioning
confidence: 99%